Association of the pri-miR-34b/c rs4938723 T > C polymorphism with hepatoblastoma susceptibility in Eastern Chinese children: A five-center case-control study - Wenli Zhang; Jinhong Zhu; Jun Bian; Chunlei Zhou; Shouhua Zhang; Shaohua He; Hongting Lu; Yizhen Wang; Jing He (BMC Medical Genomics)
Abstract Background Hepatoblastoma is the most prevalent liver cancer affecting children, and its intricate causes are closely linked to genetic variations. This study interrogated the influence of the miR-34b/c rs4938723 T > C polymorphism in hepatoblastoma predisposition in a Han Chinese children study population, comprising 193 cases and 773 controls from East China. Methods Genotyping was performed via the TaqMan technique. The association between this genetic variant and hepatoblastoma susceptibility was determined via logistic regression models adjusted for age and sex. Results Our results show that the TC genotype of the miR-34b/c rs4938723 polymorphism is associated with a significantly reduced risk of hepatoblastoma under a heterozygous model (adjusted OR = 0.59, 95% CI = 0.41–0.84, P = 0.003), whereas the CC genotype is associated with an increased risk under a recessive model (adjusted OR = 1.79, 95% CI = 1.17–2.73, P = 0.008). Further stratified analysis revealed that the TC/CC genotypes were linked to a lower risk of hepatoblastoma in girls and those with advanced clinical stages (III + IV). Furthermore, we identified the miR-34b/c rs4938723 polymorphism as an expression quantitative trait locus that affects the expression of nearby genes. The CC genotype was related to a decrease in LAYN expression in the colon, brain, and lung and decreased PPP2R1B expression in the testis. These findings suggest that miR-34b/c rs4938723 T > C has the potential to modify hepatoblastoma predisposition through its regulatory effects on gene expression. Conclusions This study provides evidence for the association between the miR-34b/c rs4938723 polymorphism and hepatoblastoma risk in Chinese Han children from East China, suggesting that this polymorphism may have potential as a biomarker for predicting hepatoblastoma susceptibility in this specific population.